Risk factors for cefotaxime resistance in children with pneumonia - Anak Agung Made Sucipta; Ida Bagus Subanada; Samik Wahab (Paediatrica Indonesiana, 2012)
Background Pneumonia is a health problem in developingcountries, often caused by bacterial agents. The 'Widespreaduse of cefotaxime, a thirdô€’generation of cephalosporin, may leadto increased incidence of resistance to this antibiotic. Severalstudies have reported on risk factors associated v.ith resistanceto cefotaxime.Objective To identify risk factors for cefotaxime resistance inchildren 'With pneumonia.Methods We performed a caseô€’control study at Sanglah Hospitalbetween January 2006ô€’December 2010. The case group includedchildren with blood cultureô€’positive pneumonia and resistanceto cefotaxime by sensitivity test. The control group was selectedfrom the same population as the case group, but the bacteriaisolated from these subjects were sensitive to cefotaxime. Wetested the folloMng risk factors for resistance to cefotaxime:age :53 years, microorganism species, history of antimicrobialuse, and history of hospitalization within the prior 3 months.Chi square test and logistic regression analysis were performedto determine any associations between the four potential riskfactors and resistance to cefotaxime. A P<0.05 was consideredto be statistically significant.Results Univariate analysis showed that the risk factors forresistance to cefotaxime were history of antimicrobial use in theprior 3 months (OR 2.79; 95%CI 1.40 to 5.55; Pô€“O.OOI) andhistory of hospitalization Mthin the prior 3 months (OR 5.57;95%CI 1.95 to 15.87; P=<O.OOOl). By multivariate analysis,risk factors associated Mth resistance to cefotaxime were historyof antimicrobial use in the prior 3 months (OR 2.4; 95%CI 1.18to 4.86; P=0.015), history of hospitalization within the prior 3months (OR 4.7; 95%CI 1.62 to 13.85; Pô€“0.004), and historyof breast feeding for less than 2 months (OR 2.3; 95%CI 1.0 to5.4; Pô€“0.042).Conclusion History of antimicrobial use and history ofhospitalization within the prior 3 monthsweresignificantriskÂ factors for resistance to cefotaxime in children Mth pneumonia.[Paediatr Indanes. 2012;52:255-9].